2008
DOI: 10.1177/1049732308315734
|View full text |Cite
|
Sign up to set email alerts
|

HPV and Cervical Cancer Testing and Prevention: Knowledge, Beliefs, and Attitudes Among Hispanic Women

Abstract: Cervical cancer is a preventable disease resulting from infection with high-risk types of sexually transmitted human papillomaviruses (HPVs). Public knowledge of HPVs and their link to cervical cancer is limited. Participation in cervical cancer prevention programs, including Pap and HPV screening and HPV vaccine acceptance, is crucial for limiting the incidence of cervical cancer. Hispanic women suffer the highest cervical cancer incidence rates in the United States. In this study, we conducted community-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 50 publications
6
91
0
Order By: Relevance
“…[12], [13] It was observed that 61% of women practiced unprotected sexual intercourse and only 39% women used condoms during intercourse. On the basis of these findings it can be expected that the knowledge regarding prevention of disease in general population is also less in our region.…”
Section: Discussionmentioning
confidence: 99%
“…[12], [13] It was observed that 61% of women practiced unprotected sexual intercourse and only 39% women used condoms during intercourse. On the basis of these findings it can be expected that the knowledge regarding prevention of disease in general population is also less in our region.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies exploring patient barriers to cervical cancer screening [11][12][13][14][15] , attitudes and beliefs about human papilloma virus (HPV) and the HPV vaccine [16][17][18] ; however, few have focused on barriers to follow-up of an abnormal Pap smear 3,6,7,16 . Del Carmen and colleagues explored sociodemographic and knowledge differences between Latina and non-Latina women referred to colposcopy 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Low levels of HPV and HPV vaccine awareness and knowledge among Latinos in a variety of U.S. regions have been demonstrated in several studies. [9][10][11] However, a number of studies showed that when the HPV vaccine is presented as a strategy to prevent cervical cancer, support for vaccine uptake is high among Latinas and Latino parents. 10,12,13 Collaborations with community-based partners who can inform the style, content, and relevancy of cancer education messages result in the most effective cancer prevention outreach efforts.…”
mentioning
confidence: 99%